2015
DOI: 10.1016/j.yebeh.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, prospective, exploratory study of patients with epilepsy switching from levetiracetam to brivaracetam

Abstract: We evaluated nonpsychotic behavioral adverse events (BAEs) in patients receiving levetiracetam (LEV) who switched to brivaracetam (BRV). Patients ≥16 years of age, receiving 2-3 antiepileptic drugs (AEDs), including LEV 1-3g/day, and experiencing BAEs within 16 weeks of LEV treatment initiation, enrolled in an open-label Phase 3b study (NCT01653262) comprising a ≤1-week screening period, an immediate switch from LEV to BRV 200mg/day (without titration), and a 12-week treatment period. The percentages of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 16 publications
(16 reference statements)
8
89
1
2
Order By: Relevance
“…Patients never previously exposed to LEV seem to have an intermediate risk of developing BAE in 15.3% (4/26) of the cases. The amelioration of BAE due to switch from LEV to BRV has already been studied in an open‐label, prospective, exploratory study . Patients underwent an immediate switch from LEV 1–3 g/day to BRV 200 mg/day without titration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients never previously exposed to LEV seem to have an intermediate risk of developing BAE in 15.3% (4/26) of the cases. The amelioration of BAE due to switch from LEV to BRV has already been studied in an open‐label, prospective, exploratory study . Patients underwent an immediate switch from LEV 1–3 g/day to BRV 200 mg/day without titration.…”
Section: Discussionmentioning
confidence: 99%
“…BRV showed promising results in clinical trials and had low discontinuation rates . According to a smaller scope study in 29 patients, an immediate switch from LEV to BRV seems feasible without titration and might alleviate LEV‐induced behavioral adverse events (BAEs) . The main treatment‐emergent adverse events (TEAEs) observed during the regulatory trials were somnolence, dizziness and psychobehavioral symptoms …”
mentioning
confidence: 99%
“…The most serious adverse effects of levetiracetam are behavioral in nature and are more common in children and in adult epilepsy patients with a prior history of behavioral problems and psychiatric disease [110]. The more selective SV2A mechanism of brivaracetam versus levetiracetam triggered UCB to perform a small, open-label study to assess if brivaracetam may be associated with fewer behavioral adverse effects [111]. This study showed that epilepsy patients experiencing behavioral adverse effects associated with levetiracetam benefited from switching to brivaracetam.…”
Section: Preclinical and Clinical Profile Of Levetiracetam And Its Comentioning
confidence: 99%
“…It may be dosed at 25‐100 mg twice daily. It is an attractive alternative to LEV for patients experiencing psychiatric side effects …”
Section: Introductionmentioning
confidence: 99%